2017
DOI: 10.3389/fneur.2017.00516
|View full text |Cite
|
Sign up to set email alerts
|

Chronic 5-Aminoimidazole-4-Carboxamide-1-β-d-Ribofuranoside Treatment Induces Phenotypic Changes in Skeletal Muscle, but Does Not Improve Disease Outcomes in the R6/2 Mouse Model of Huntington’s Disease

Abstract: Huntington’s disease (HD) is an autosomal dominant neurodegenerative genetic disorder characterized by motor, cognitive, and psychiatric symptoms. It is well established that regular physical activity supports brain health, benefiting cognitive function, mental health as well as brain structure and plasticity. Exercise mimetics (EMs) are a group of drugs and small molecules that target signaling pathways in skeletal muscle known to be activated by endurance exercise. The EM 5-aminoimidazole-4-carboxamide-1-β-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…Another proposed therapeutic agent for HD, a p75 neurotrophin receptor ligand, LM11A-31, demonstrated an increase in mean survival of 17 days in R6/2 mice 28 . Many other studies have not investigated or reported survival29, 30 or failed to see an improvement in survival after treatment 31, 32…”
Section: Discussionmentioning
confidence: 99%
“…Another proposed therapeutic agent for HD, a p75 neurotrophin receptor ligand, LM11A-31, demonstrated an increase in mean survival of 17 days in R6/2 mice 28 . Many other studies have not investigated or reported survival29, 30 or failed to see an improvement in survival after treatment 31, 32…”
Section: Discussionmentioning
confidence: 99%